Catalytic Effect of Mn2+ on Oxidative Deamination and Decarboxylation L-isomers of Amino Acids by Permanganate - Sahu, B.R.; R. Chourey, Vijay; Pandey, Shakuntala; Shastry, V.R. (Asian Journal of Chemistry, 2010)
Investigation of catalytic effect of Mn2+ on oxidative deaminationand decarboxylation of L-isomers of amino, acids was carriedout by iodometric estimations.